Seesaw tau lepton mass and calculable neutrino masses in a 3-3-1 model - Montero, J. C. [UNESP]; De, C. A. [UNESP]; Pleitez, V. [UNESP] (American Physical Society (APS), 2002)
In this work we show that in a version of the 3-3-1 model proposed by Duong and Ma, in which the introduction of a scalar sextet is avoided by adding a singlet heavy charged lepton, the τ lepton gains mass through a seesawlike mechanism. We also show how to generate neutrino masses at the one-loop level, and give the respective Maki-Nakagawa-Sakata mixing matrices for a set of the parameters. We also consider the effect of adding a singlet right-handed neutrino.